Distance Learning for Children with Autism Spectrum Disorders - Oom Sitti Homdijah; Euis Heryati; Ehan; Mughi Puspa Annisi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
One of the impacts of the covid 19 pandemic is that schools are closed, and students are asked to study at home. This condition affects students with autistic spectrum disorders. Distance learning (PJJ) makes students with autistic spectrum disorders uncomfortable, often tantrums, and become more frustrated. This condition is why researchers examine the implementation of distance learning for children with autistic spectrum disorders. This study aims to analyze PJJ in children with autistic spectrum disorders. This research used a qualitative approach. Data collection was carried out using interview and questionnaire methods. The subjects of this study were teachers of children with special needs for children with autistic spectrum disorders (ASD) in schools. The analysis used qualitative analysis. The results showed that the PJJ online learning process mostly used WhatsApp. It is due to limitations on facilities for online learning, limited knowledge and skills of parents to use PJJ process facilities, and some teachers who need to be more skilled in carrying out the PJJ process. Online training or seminars are needed as an approach to parents to provide the understanding and improve teacher skills in PJJ. The results of this study are expected to facilitate parents and teachers in PJJ, especially for children with autistic disorders